Demotivation in Arabic Learning among University Students l Al-Tatsbith fi Ta’allum al-Lughah al-‘Arabiyah lada Tullab al-Jami‘ah - Hijriyah, Athiyah Laila; Haris, Abdul; Firdaus, Mochammad; Rusdi, Rusdi; A Alturki, Adel Ibrahem (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
One of the things that often hinders success in learning Arabic is the emergence of demotivation. This study aims to analyze the form of demotivation and understand the factors that cause demotivation in learning Arabic for students of the Arabic Language Development Program (PPBA) at the Universitas Muhammadiyah Malang. This research used a qualitative approach with the type of case study. The subjects in this study were ten PPBA students and lecturers at the Universitas Muhammadiyah Malang. To collect data, the researchers observed students who were demotivated in learning Arabic, also asked the lecturers and program managers about this phenomenon, and saw the related documents. In addition, to analyze the data, the researcher used Miles and Huberman's interactive technique with the stages of reducing data that is less relevant to the research objectives, displaying it in the form of tables and narratives, then making conclusions. The researchers used source triangulation and member check techniques to test the validity of the data. The results indicated that there were types of demotivation that faced by students and there are factors that cause demotivation in students learning Arabic at PPBA. This research contributed in mapping the types of demotivation and its factors experienced by many students in learning Arabic.